THE POWER OF IDEAS. THE INFLUENCE OF HASSAN AL-BANNA AND SAYYID QUTB ON THE MUSLIM BROTHERHOOD ORGANIZATION - Azoulay, Ronnie (Przegląd Strategiczny, 2015)
This article analyzes the ideological influences of Egyptian leaders Hassan al-Banna and Sayyid Qutb on the Muslim Brotherhood. Al-Banna and Qutb are considered by many scholars as prominent thinkers in the Muslim world of the twentieth century. They have had a major impact on Islamic extremism in modern times, and have dealt with a number of religious and social issues, which exist in Islamic discourse until today. On the one hand, many of their writings were written metaphorically, while on the other hand, their writings are interpreted by many as explicit orders to exercise violence. This article examines whether Qutb and al-Banna’s ideas still have actual impact on the Egyptian Muslim Brotherhood. The aim is to make a case for assuming a new standpoint, which will add to the wider research knowledge.